Improving Social Aspects Through Play Therapy in Children with Autism Disorder - Sanjaya, Budi; Cahyati, Yanti; Adhe Marsanda, Diva; Putri, Vani Dwi (International Journal of Advanced Multidisciplinary, 2024)
Autism is one of the pervasive developmental disorders in which children express behavior that is unable to hold social interactions and as if they live in their world. The prevalence of children with Autism is increasing, and so therapy is needed to return the child to normal. Several studies say that play therapy can improve social aspects in children with Autism. This research is a literature review of 20 articles. Articles were searched through Google Scholar with the keywords play therapy, social elements, and Autism, and 20 articles that met the inclusion and exclusion criteria were selected. The results of a review of 20 articles stated an increase in social aspects in children with Autism through play therapy. There was a correlation from various studies related to the effect of increasing social elements in children with autism disorders through play therapy. There was an increase in social aspects in children with Autism through play therapy.